Clinical and Preclinical Therapies for Bladder Cancer Following Bacillus Calmette-Guérin Failure. Issue 1 (6th January 2023) - Nazmifar, Michael; Williams, Cheyenne; Naser-Tavakolian, Aurash; Heard, John; Rosser, Charles; Theodorescu, Dan; Ahdoot, Michael
Abstract : Purpose: Intravesical bacillus Calmette-Guérin is the current first-line treatment for high-grade nonmuscle-invasive bladder cancer; however, a substantial proportion of patients are unresponsive to bacillus Calmette-Guérin treatment. While cystectomy is often recommended in bladder cancer following bacillus Calmette-Guérin failure, there are numerous established therapeutic agents and pre-commercialized trials describing treatments for nonmuscle-invasive bladder cancer following failed bacillus Calmette-Guérin treatment. Our objective in this systematic review is to characterize the efficacy of these therapeutic agents by reporting their corresponding complete response rates and toxicity profiles. Materials and Methods: We conducted a systematic review of all available clinical trials evaluating therapies to treat recurring nonmuscle-invasive bladder cancer after previous intravesical bacillus Calmette-Guérin. Bacillus Calmette-Guérin failure patients who had previously failed 1 or more courses of prior bacillus Calmette-Guérin therapy were included. Studies that were not in the English language, included muscle-invasive bladder cancer patient populations, or lacked a post-treatment evaluation of response were excluded. We used PubMed/Medline, the Cochrane Library, and Embase to search for relevant studies. No formal risk of bias assessment was conducted. Complete response rates for 3, 6, 12, and 24 months post-treatment evaluation, progression rates, cystectomy rates, and 12 complications are reported. Results: A total of 70 studies with 73 reports evaluating 27 treatment options were retained for final analysis. These treatments were reported in 5 categories including intravesical chemotherapy, combination therapy, hyperthermia paired with intravesical chemotherapy, immunotherapy, and novel agents, with published years ranging from 1998 to 2021. Single intravesical chemotherapy and the combination of multiple intravesical chemotherapy agents demonstrate varied complete response rates of 10%-83% at 12 months. Limited clinical data evaluating hyperthermia paired with chemotherapy demonstrate 12-month complete response rates of 50%-85%. Despite these reported response rates, progression rates ranged from 0%-18%. Moreover, immunotherapeutic agents demonstrate progression rates of 7% to 22% at a median of 12 months of follow-up. Novel agents displayed a wide range of complete response rates (6% to 91%) at 12 months based on the treatment used. Total grade 3 toxicity rates range from 0%-55% for intravesical chemotherapy and combination intravesical chemotherapy agents, 0%-15% for hyperthermia paired with chemotherapy agents, 12%-13% for immunotherapy agents, and 0%-17% for novel agents. Conclusions: Bladder-preserving treatments accomplish moderate success in nonmuscle-invasive bladder cancer following bacillus Calmette-Guérin failure. As the majority of available clinical trials are single-armed uncontrolled cohorts and contain a limited number of patients, strength and comparability of the data are limited. In general, intravesical chemotherapy and hyperthermia paired with mitomycin C demonstrate some of the highest complete response rates at 12 and 24 months. Similarly, among the pre-commercialized novel agents, N-803 and gene therapy display promising results and may serve as potential future treatment for nonmuscle-invasive bladder cancer following failed bacillus Calmette-Guérin treatment. In terms of toxicity/complication rates, both commercially available and unavailable treatments showcase low toxicity profiles for bladder cancer following bacillus Calmette-Guérin failure. The comprehensive analysis provided by this systematic review can serve as a reference for treatment decisions and clinical trial design in the bacillus Calmette-Guérin-unresponsive domain.